Attention and Visuospatial Working Memory Share the Same Processing Resources - Feng, Jing; Pratt, Jay; Spence, Ian (Frontiers in Psychology, 2012)
Attention and visuospatial working memory (VWM) share very similar characteristics; both have the same upper bound of about four items in capacity and they recruit overlapping brain regions. We examined whether both attention and visuospatial working memory share the same processing resources using a novel dual-task-costs approach based on a load-varying dual-task technique. With sufficiently large loads on attention and VWM, considerable interference between the two processes was observed. A further load increase on either process produced reciprocal increases in interference on both processes, indicating that attention and VWM share common resources. More critically, comparison among four experiments on the reciprocal interference effects, as measured by the dual-task costs, demonstrates no significant contribution from additional processing other than the shared processes. These results support the notion that attention and VWM share the same processing resources.